2017
DOI: 10.1039/c7ta05583h
|View full text |Cite
|
Sign up to set email alerts
|

Low band gap conjugated polymers combining siloxane-terminated side chains and alkyl side chains: side-chain engineering achieving a large active layer processing window for PCE > 10% in polymer solar cells

Abstract: Side-chain random copolymers show high 3-D hole transport and offer excellent active layer thickness tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
98
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 57 publications
1
98
1
Order By: Relevance
“…This trend indicates that a lower degree of polymerization was achieved for polymers with higher siloxane content, but that these nevertheless show a higher tendency for aggregation in o-DCB at elevated temperature. The difference in degree of polymerization could therefore be related to premature aggregation in the polymerization mixture, thereby inhibiting the reaction, an effect previously observed by Liu et al, 27 indicating that polymer solubility during polymerization can have an effect on molecular weight obtained. This implies that polymers with a high siloxane content have a low intrinsic and overall solubility coupled with a low M p , whereas polymers with a low siloxane content have higher intrinsic and overall solubilities coupled with a high M p .…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…This trend indicates that a lower degree of polymerization was achieved for polymers with higher siloxane content, but that these nevertheless show a higher tendency for aggregation in o-DCB at elevated temperature. The difference in degree of polymerization could therefore be related to premature aggregation in the polymerization mixture, thereby inhibiting the reaction, an effect previously observed by Liu et al, 27 indicating that polymer solubility during polymerization can have an effect on molecular weight obtained. This implies that polymers with a high siloxane content have a low intrinsic and overall solubility coupled with a low M p , whereas polymers with a low siloxane content have higher intrinsic and overall solubilities coupled with a high M p .…”
Section: Resultsmentioning
confidence: 75%
“…Also in solar cells siloxane containing polymers have been introduced to increase crystallinity of the electron donor, inuencing the morphology of the blend layers. [25][26][27][28] This has led to highly performance solar cells, with PCE of 11%, when siloxane side chains were combined with regular alkyl chains within the same polymer. 27 Interestingly, it was shown that the number average molecular weight (M n ) decreased with increasing siloxane content, as polymers with high siloxane content were less soluble and could not reach high M n 's before becoming insoluble.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8] Significant research effortsh ave been devoted to developing donor-acceptor (D-A)-typec opolymers with ab road light absorption spectrum and ah igh charge-carrier mobility. [5,7,9,10] Benzo [1,2-b:4,5-b']dithiophene (BDT) and dithieno[2,3-d:2',3'-d']benzo [1,2-b:4,5-b']dithiophene( DTBDT) derivatives have been widely used as electron-donating units in polymers emiconductors. [7,8,[10][11][12] Composed of fused aromatic and planar core units,t hese derivativesd isplay high charge-charierm obility.…”
Section: Introductionmentioning
confidence: 99%